Introducing the medieval ass - Smithies, Kathryn L. (Medieval animals., 2020)
"Introducing the Medieval Ass presents a lucid, accessible, and comprehensive picture of the enormous socioeconomic and cultural significance of the ass, or donkey, in the Middle Ages and beyond. In medieval times, the ass was a vital, utilitarian beast of burden, rather like ubiquitous white delivery vans today. At the same time, however, the ass had a rich, paradoxical reputation. Its hard work was praised but its obstinacy condemned. It exemplified the good Christian, humbly bearing Christ to Jerusalem, but also represented sloth, a mortal sin. It had a potent sexual reputation--in one literary work, an ass had sex with a woman--even as it was simultaneously linked to sterility. Over time, the ass also became synonymous with human idiocy, a comic figure representing foolish peasants, students too dull to learn, and their asinine teachers. This trope of foolishness was so prevalent that by the eighteenth century the word "ass" began to be replaced by "donkey." Introducing the Medieval Ass offers a wide-ranging account of the importance, and often surprising cultural prevalence, of this common domesticated animal."